The ultimate goal and the theological pursuit according to Saint Thomas: between intellectualism and voluntarism - Yangali Núñez, Oscar Edmundo (2019)
In this work, I develop the importance of Thomas Aquinas’ reflection on the relationship between understanding and will with respect to the theological work. I examine first the so-called intellectualism of St. Thomas. Then, I proceed to discuss and resolve what the Thomistic conception of essence consists of. And finally, I present the contribution that the love of charity represents in the theological pursuit. I conclude that the thought and timeliness of St. Thomas for theology resides in an essential unity, a metaphysical and anthropological basis, which establishes a relationship between the understanding of the doctrine and the experience of the Gospel based on the love of charity.